Origin of trace elements in the Vestfold saline lake waters, Princess Elizabeth Land (extended abstract) - Masuda, Noriyasu; Nakaya, Shyu; Burton, Harry R.; Torii, Tetsuya (1985)
P(論文) departmental bulletin paper